Hambatan Oklusi dan Artikulasi Sebagai Faktor Trauma Oklusi Sekunder pada Pasien Periodontitis: Tinjauan Pustaka - Dwi Aprilia, Selly; Nauli Komala, Olivia (Jurnal Kedokteran Gigi Terpadu, 2025)
Occlusal trauma is a pathological condition that occurs as a result of excessive occlusal forces that exceed the adaptive capacity of the periodontal tissues. Although not the primary cause of periodontitis, occlusal trauma can exacerbate existing periodontal inflammation and accelerate the destruction of supporting tooth structures. Occlusal interferences, such as premature contacts, as well as articulation interferences or blocking during mandibular movements, are factors that can increase the mechanical load on the periodontium. These disturbances may lead to secondary occlusal trauma in teeth with compromised periodontal support. Understanding occlusal and articulation interferences is essential for maintaining periodontal health, as proper occlusal adjustment and functional balance can help prevent further damage to the tooth-supporting tissues. This study aims to review the role of these interferences on secondary occlusal trauma in periodontitis patients.